2019
DOI: 10.1111/ctr.13764
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C donor viremic cardiac transplantation: A practical approach

Abstract: Introduction Patients with end‐stage heart failure eligible for orthotopic heart transplantation (OHT) exceed the number of available donor organs. With highly effective hepatitis C virus (HCV) antiviral therapy now available, HCV+ organs are increasingly utilized. We seek to describe our experience with patients receiving HCV viremic organs as compared to non‐HCV transplant recipients. Methods Our center began utilizing HCV hearts in February 2018. We retrospectively reviewed baseline demographics, laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Our initial search terms resulted in a set of 2186 articles, of which 35 studies satisfied the inclusion and exclusion criteria (Figure 1), 13‐46 including one paper identified with reference search 47 . There were 852 SOTs, which included 343 kidney, 233 heart, 204 liver and 72 lung transplants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our initial search terms resulted in a set of 2186 articles, of which 35 studies satisfied the inclusion and exclusion criteria (Figure 1), 13‐46 including one paper identified with reference search 47 . There were 852 SOTs, which included 343 kidney, 233 heart, 204 liver and 72 lung transplants.…”
Section: Resultsmentioning
confidence: 99%
“…There was one case of viral relapse, successfully retreated and achieved SVR12 (Table 2). 25 A total of 12 deaths occurred. Five deaths were from primary graft failure, one death from graft dysfunction, 45 one from a pulmonary embolism, 26 one from disseminated bacteremia, 27 one from heart failure, 22 two deaths from necrotizing pancreatitis 39,46 and one death from multi‐organ failure with antibody‐mediated rejection 24 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given these promising findings, there has been rapidly growing interest in using hearts from HCV-positive donors. Several reports have demonstrated similar survival, as well as similar incidence of acute rejection and malignancy, in recipients of HCV-positive donor hearts who were treated with direct-acting antivirals after transplant, compared to those who received HCV-negative donor organs [37,38]. The largest study to date is a prospective observational cohort from Vanderbilt University that reported outcomes on 80 recipients of HCV-positive donor hearts from 2016 to 2019 [39••].…”
Section: Donors With Hepatitis Cmentioning
confidence: 99%